Adjusting the management of the Antarctic krill fishery to meet the challenges of the 21st century - Bettina Meyer; Javier A. Arata; Angus Atkinson; Dominik Bahlburg; Kim Bernard; César A. Cárdenas; Susie M. Grant; Simeon L. Hill; Lukas Hüppe; Taro Ichii; So Kawaguchi; Bjørn A. Krafft; et al. (Proceedings of the National Academy of Sciences, 2025)
Antarctic krill ( Euphausia superba ) is the central prey species in the Southern Ocean food web, supporting the largest and fastest-growing fishery in the region, managed by the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). Climate change is threatening krill populations and their predators, while current catch limits do not take into account climate variability or krill population dynamics. In 2024, CCAMLR was unable to renew its spatial catch limits, highlighting the urgent need for improved management of the krill fishery to prevent any harm to the Southern Ocean ecosystem. To address this, we propose a management framework that integrates variability in krill recruitment and key pathways between spawning and nursery areas—a krill stock hypothesis—to inform decisions on catch limits and conservation measures. Implementing this approach will require targeted data collection, which we propose can be achieved through a multisector collaborative network that combines traditional and new technologies, including the use of fishing vessels as data collection platforms. We use case studies to demonstrate how fisheries can contribute to data collection while promoting sustainable management. A major challenge in this effort is securing long-term funding for data collection, which is critical for managing climate-sensitive populations of high commercial interest. We therefore recommend using the industry as a source of funding, research platform and data provider, alongside national research funding opportunities. Given the fundamental role of krill in the Southern Ocean ecosystem, its decline would have cascading effects on predators and essential ecosystem services.